Effects of the two consecutive anaerobic exercise sessions on leukocyte subsets distribution, blood lactate level and anaerobic power in female athletes with controlling the confounding effect from plasma shift - Karim Azali Alamdari; Hadi Rohani; Zeynab Bagheri (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2020)
Background: The majority of existing data concerning the leukocyte subsets distribution after daily consecutive exercise sessions are controversial because of the confounding effect of plasma shift into active muscles. The aim of this study was to investigate the Effects of the two consecutive anaerobic exercise sessions on leukocyte subsets distribution, blood lactate level and anaerobic power in female athletes with controlling the confounding effect from plasma shift. Methods: This was an experimental study in which 30 subjects were randomized into experimental(EX) and control(Con) groups after body composition measurements and the Ex group experienced two anaerobic sessions (at 9.00 am and 15 pm),. Blood samples were taken before and after each session. Results: Both session elevated blood leukocytes and their subpopulations (monocytes, lymphocytes and granulocytes) count as well as blood lactate levels (P<0.05). Following to the first session, the increasing trend in leukocyte and granulocytes count was continued, however; the monocytes count and blood lactate levels returned to baseline level, while lymphocytes count was reached to levels even lower than baseline values (P<0.05). The mean and min power in the second session were lower than the morning session (P<0.05). Conclusion: Although the effects of two consecutive sessions to induce leukocytosis and a consequent lymphocytopenia in elite female athletes was verified even after controlling of the confounding effect of plasma shift, however; because of the lack of similar evidences and some of methodologic limitations, more researches still remains to be done.